Ultrasonographic evaluation of diastasis recti abdominis and its association with pelvic floor dysfunction in postpartum women: a cross-sectional study of a two-year retrospective cohort - Li, Manrong; Wang, Nana; Wang, Rui; Liang, Bingyin (Frontiers in Medicine, 2024)
Objective: This study aims to evaluate the ultrasonographic findings of Diastasis Recti Abdominis (DRA) in postpartum women, explore associated risk factors, and assess the relationship between DRA and pelvic floor dysfunction.This retrospective cross-sectional study included 143 parturient women diagnosed with DRA at our institution from January 2022 to December 2023. The study aimed to assess the ultrasonographic characteristics and clinical implications of DRA in postpartum women. The study participants were aged 21-43 years, carried a single fetus to term without instrumental delivery, and had no prior abdominal surgery.We excluded incomplete records and cases with congenital lumbar spine abnormalities or significant visceral disease. Ultrasound was employed to evaluate the DRA features, specifically the condition of the abdominal midline and echo types. A control group comprised 57 women who had normal deliveries without DRA. The primary outcome of this study was the measurement of rectus abdominis separation using ultrasonography. Secondary outcomes included the assessment of pelvic floor muscle function via electromyography (EMG), evaluation of pain levels, and the identification of risk factors associated with diastasis recti.In the observation group, ultrasound revealed widened abdominal midlines in 122 cases (85.31%), discontinuity in 21 cases (14.68%), and various echo types indicating unequal, narrow band-like moderate, and slightly strong fibrous echoes.Significant differences were found in rectus abdominis separation and levator ani muscle hiatus area, with both being larger in the observation group compared to the control group (p < 0.05). Advanced maternal age, higher parity, higher pre-pregnancy BMI, and cesarean delivery were identified as significant risk factors for DRA occurrence in the logistic regression analysis.DRA is prevalent among postpartum women with specific ultrasonographic profiles indicating considerable abdominal muscle separation. The study highlights the importance of ultrasound in diagnosing DRA and suggests that certain demographic and delivery method factors increase the risk of this condition.These findings could guide clinicians in early diagnosis and intervention, potentially improving outcomes for affected women.